Air pollution control strategies directly limiting national health damages in the US - Yang Ou (Nature Portfolio, 2020)
Decoupling emission reduction target determination, air pollution modelling, and health benefit estimation complicates control strategy design. Here an integrated approach identifies strategies to reduce health damages of air pollution, showing that benefits can be achieved cost-effectively by electrifying sources with high primary PM2.5 emission intensities.